2020
DOI: 10.1017/aer.2020.126
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutant emissions from aircraft landing and take-off cycles at Chinese airports

Abstract: Research on flight emissions at airports is very important for environmental policymaking. This study analysed the trend of aircraft air pollutant emissions at mainland China airports from 1990 to 2017, mainly focusing on standard landing and take-off (LTO) cycles. Total flight movements increased 29-fold from 1990 to 2017 at Chinese airports. Over the same period, the emissions of NOx, SOx, CO, hydrocarbons (HC), and particulate matter (PM) increased 46, 27, 12, 5, and 4 times, respectively. Emissions at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Similarly, for the air pollutants CO, PM and SO 2 , the results of this study were higher than those of [28,50,56,57], which were 3-126%, 16-290% and 127-1381%, respectively. For the LTO phase, the CO 2 emissions were 20% higher than the results of [58], for the air pollutants CO, PM, SO 2 and NOx, the results of this study were higher than those of [18,58], which were 41-77%, 100-300%, 58-533%, 0.85-57%, respectively. The reasons for the differences may be attributed to the following: (1) Interannual variation in activity levels, as the emission inventories in these studies were established 0-8 years prior to this study, which can explain the annual increase in pollutant emissions.…”
Section: Present Emissions From the Aviation Sectorcontrasting
confidence: 65%
“…Similarly, for the air pollutants CO, PM and SO 2 , the results of this study were higher than those of [28,50,56,57], which were 3-126%, 16-290% and 127-1381%, respectively. For the LTO phase, the CO 2 emissions were 20% higher than the results of [58], for the air pollutants CO, PM, SO 2 and NOx, the results of this study were higher than those of [18,58], which were 41-77%, 100-300%, 58-533%, 0.85-57%, respectively. The reasons for the differences may be attributed to the following: (1) Interannual variation in activity levels, as the emission inventories in these studies were established 0-8 years prior to this study, which can explain the annual increase in pollutant emissions.…”
Section: Present Emissions From the Aviation Sectorcontrasting
confidence: 65%
“…The assessment of emissions generated by aircraft at ground level is largely described in the literature from different points of view. Specific assessments due to Landing and Take-Off (LTO) cycles in several case studies are available, stressing the relevance of including specific parameters such as the detailed flight information and the dynamic time in climb and approach modes [8], aircraft fleets performance and payload [9], availability of runways [10], considering specific inventories [11,12], large-scale benchmark [11,13,14], or case-specific assessments. All highlight how LTO operations might affect air quality and increase noise levels, eventually impacting public health [15,16].…”
Section: The Airport As An Environmentally Sensitive Areamentioning
confidence: 99%
“…It was found that monthly and daily emissions do not vary significantly. Yu et al ( 2021 ) analyzed the trend of AEEs at some airports in mainland China from 1970 to 2017 and found that the average emission per passenger has declined for the duration. Bao et al ( 2021 ) revealed some simple regional distribution of AEEs from LTO cycles during the pandemic but failed to thoroughly compare the AEEs at airports in 2020 to the year when the pandemic had not yet occurred.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, this study intends to explore the positive environmental impacts of travel restrictions from the perspective of AEEs at the ground level. Although several researches have focused on the estimation and analysis of AEEs from LTO cycles at both the local scale (Yılmaz 2017 ; Kuzu 2018 ; Tokuslu 2020 ) and the regional scale (Kesgin 2006 ; Hu et al 2020 ; Yu et al 2021 ), the research on AEEs from LTO cycles in the context of the COVID-19 pandemic is still scarce. Furthermore, there has never been any analysis of the relative change in air pollution at airports between the COVID-19 era and the pre-COVID-19 era, either from a temporal or spatial perspective.…”
Section: Introductionmentioning
confidence: 99%